Mental Health as Public Health Interdisciplinary Perspectives on the Ethics of Prevention, Volume 2 (London Elsevier/Academic Press, 2019)
In recent years there has been increased recognition of the global burden of mental disorders, which in turn has led to the expansion of preventive initiatives at the community and population levels. The application of such public health approaches to mental health raises a number of important ethical questions. The aim of this collection is to address these newly emerging issues, with special attention to the principle of prevention and the distinctive ethical challenges in mental health. The collection brings together an interdisciplinary group of experts in bioethics, mental health, public health, and global health. Compared to other public health initiatives, those directed towards mental health are relatively new and have yet to receive sustained ethical analysis. This is the first edited volume to highlight the distinctive ethical issues surrounding public mental health. The individual chapters contain cutting-edge, original research by an interdisciplinary collection of authors, including experts in bioethics, mental health, public health, and global health.
English
Keywords: Mental health services; mental disorder; mental health; ethics; prevention; public health